Analyzing Feminist Discourse in a Pakistani Screenplay - Mansoor, Zahida; Khalid, Maryam (Pakistan Journal of Humanities and Social Sciences, 2024)
The study explores the feminist discourse in a Pakistani screenplay, highlighting attitudes towards women's emancipation. Using a qualitative lens, it investigates the language of the screenplay and the linguistic features that reinforce the impression of empowered Pakistani women. The thematic analysis reveals that the prevailing patriarchal cultural narratives are challenged in the screenplay, offering a departure from the predictability of the earlier storylines. The findings also indicate that changes in the way women are viewed is strengthened by the screenplay’s language choices, highlighting the acceptance of women in non-traditional roles. Defying stereotypes, through strong and capable roles, overturning the traditionally limited mindsets, the screenplay determines that women are crucial to a more inclusive society. The study concludes that in a supportive environment, with opportunities for training and development, their achievements acknowledged, and their voices heard, women thrive. There is a need for screenplays with suitable language that scaffolds an understanding for creating stories that foster a deeper comprehension of the feminine competence and abilities.